2006
DOI: 10.1038/nature04590
|View full text |Cite
|
Sign up to set email alerts
|

A silicon transporter in rice

Abstract: Silicon is beneficial to plant growth and helps plants to overcome abiotic and biotic stresses by preventing lodging (falling over) and increasing resistance to pests and diseases, as well as other stresses. Silicon is essential for high and sustainable production of rice, but the molecular mechanism responsible for the uptake of silicon is unknown. Here we describe the Low silicon rice 1 (Lsi1) gene, which controls silicon accumulation in rice, a typical silicon-accumulating plant. This gene belongs to the aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
1,086
1
21

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,411 publications
(1,147 citation statements)
references
References 21 publications
39
1,086
1
21
Order By: Relevance
“…The rice gene Lsi1 was identified using a rice mutant defective in silicon (Si) uptake (Ma et al 2006). Lsi1 belongs to the Nod26-like intrinsic protein (NIP) subfamily of aquaporins.…”
Section: B Tolerance In Barleymentioning
confidence: 99%
“…The rice gene Lsi1 was identified using a rice mutant defective in silicon (Si) uptake (Ma et al 2006). Lsi1 belongs to the Nod26-like intrinsic protein (NIP) subfamily of aquaporins.…”
Section: B Tolerance In Barleymentioning
confidence: 99%
“…Massey and Hartley (2006) demonstrated that silica in grasses not only deterred feeding by field voles, but also inhibited the growth rates of the voles by decreasing nitrogen absorption from foliage. Ma et al (2006), working with rice, identified for the first time in a higher plant a silicon transporter gene, called Lsil, that controls silica uptake. Work of this kind is the final link in establishing a molecular basis for silica uptake and for the significant variability in the amounts of phytoliths that different taxa ultimately make.…”
Section: Why Plants Make Phytolithsmentioning
confidence: 99%
“…Members of the NIP (nodulin-26-like intrinsic proteins) and PIP (plasma membrane intrinsic proteins) subfamilies of aquaporins have been shown to facilitate AsIII transport in plants in Abbreviations NIPs, nodulin-26-like intrinsic proteins; RGR, relative growth rate; WT, wild-type. addition to transporting essential nutrients such as silicon and boron [7][8][9][10][11][12][13].…”
Section: Highlightsmentioning
confidence: 99%